Analysis of Glenn Fredlly "Tinggikan" Song Lyrics: Model Teun A. Van Dijk - Muhamad Farik Soumena; Siti Ainun Jariah; Zamzani Zamzani (International Journal of Scientific Multidisciplinary Research, 2024)
This study aims to describe the lyrics of Glenn Fredly song "Tinggikan" using Van Dijk critical analysis discourse analysis. The problem that arises in this study is what are the models of Teun A. van Dijk that appear in the lyrics of the song. This research is a type of qualitative descriptive research. The subject of this study was the lyrics of the song "Tinggikan" by Glenn Fredly. Data collection techniques in this study were carried out by observation and then recording and grouping them based on the critical discourse analysis model initiated by Teun A. van Dijk.  Findings from the study show that Glenn Fredly lyrics of the song "Tinggikan" adhere to three levels of discourse analysis of Teun A. van Dijk model, namely: (1) macrostructure; (2) superstructure, and (3) microstructure